From chaos to the cosmos in the gardens of the Virreina: Echoes and mirrors in the "Loa en las huertas" by Sor Juana Ines de la Cruz - Sancho Dobles, Leonardo (2019)
It offers an approach to the “Loa en las huertas da donde fue a divertirse la excelentísima señora Condesa de Paredes, Marquesa de la Laguna” the short play uses characters taken from the classical mythology and takes to the stage in the structural plane a game of repetitions. The way in which these repetitions work at the acoustic, visual and symbolic level is explored.